Optimasi Pengelolaan Presensi Siswa Menggunakan Excel dan Visual Basic : (Studi Kasus di SMK Kesehatan Anigou Nabire) - Heris Yosua Ramase Rony; Arief Rahman Hakim (STMIK Pesat Nabire, 2024)
The research aims to optimize student absence management at the Anigou Nabire High School of Health Professionals through the development of an Excel and Visual Basic based system using the Prototype method. The system is designed to improve accuracy and efficiency in the recording and processing of student presence data, replacing the manual methods that are vulnerable to errors. The Prototipe method is chosen to enable iterative development with user feedback, thus producing a system that is more tailored to the needs of the end user. Test results show that the system improves data accuracy, speeds up processing time, and makes it easier for teachers and administrative staff to use. Thus, the study concluded that the absence system based on Excel and Visual Basic with the Prototype method could be an effective solution to addressing the problem of student absence management and could be adopted by other schools facing similar challenges.